Antepartum evaluation of the obstetric conjugate at transabdominal 2D ultrasound: A feasibility study. (26th July 2021) - Di Pasquo, Elvira; Volpe, Nicola; Labadini, Corinne; Morganelli, Giovanni; Di Tonto, Andrea; Schera, Giovanni B. L.; Rizzo, Giuseppe; Frusca, Tiziana; Ghi, Tullio
Abstract: Introduction: The obstetric conjugate represents the shortest anteroposterior diameter of the birth canal and it reflects the capacity of the pelvic inlet to allow the passage and the engagement of the fetal head. The antepartum evaluation of this parameter may be attempted at digital examination to predict the risk of cephalopelvic disproportion, but the accuracy of clinical pelvimetry is notoriously poor. The aim of our study was to describe the sonographic measurement of the obstetric conjugate at transabdominal 2D‐ultrasound and to assess its reproducibility. Material and methods: This is a prospective cohort study conducted at a tertiary University hospital. A non‐consecutive series of pregnant women with uncomplicated singleton pregnancies attending the antenatal clinic for routine booking from 34 weeks of gestation onward were included. The ultrasound probe was longitudinally placed above the level of the symphysis and the interpubic fibrocartilaginous disk was visualized. Then the promontory was identified as the most prominent segment of the sacral vertebral column. The obstetric conjugate was measured as the distance between the inner edge of the interpubic disk and the promontory. The inter‐ and intraobserver repeatability of this measurement was calculated using the intraclass correlation coefficient (ICC) and the Bland–Altman method. Results: In all, 119 women were considered eligible for the study; of these, 111/119 (93.3%) women were included in the analysis with a median gestational age of 36.0 (35.0–37.0) weeks. The mean obstetric conjugate measurement was 11.4 ± 0.93 cm for the first operator and 11.4 ± 0.91 cm for the second operator. The overall interobserver ICC was 0.95 (95% [confidence interval] CI 0.92–0.96) and the overall intraobserver ICC was 0.97 (95% CI 0.96–0.98). Limits of agreement ranged from −0.84 to 0.80 for interobserver measures and from −0.64 to 0.62 for intraobserver measures. The degree of reliability was also analyzed for women with a body mass index ≥30 and for women with a gestational age ≥37 weeks. The inter‐ and intraobserver ICCs were respectively 0.97 (95% CI 0.90–0.98) and 0.98 (0.95–0.99) in the former group and 0.96 (95% CI 0.93–0.98) and 0.97 (95% CI 0.95–0.98) in the latter group. Conclusions: Our study demonstrated that among pregnant women at term gestation, sonographic measurement of the obstetric conjugate is feasible and reproducible.